MJO‐Related Intraseasonal Variation in the Stratosphere: Gravity Waves and Zonal Winds. Issue 2 (19th January 2018) - Alexander, M. J.; Grimsdell, A. W.; Stephan, C. C.; Hoffmann, L.
Abstract: Previous work has shown eastward migrating regions of enhanced temperature variance due to long‐vertical wavelength stratospheric gravity waves that are in sync with intraseasonal precipitation and tropopause wind anomalies associated with the Madden‐Julian Oscillation (MJO). Here the origin of these intraseasonal gravity wave variations is investigated with a set of idealized gravity wave‐resolving model experiments. The experiments specifically test whether tropopause winds act to control gravity wave propagation into the stratosphere by a critical level filtering mechanism or play a role in gravity wave generation through an obstacle source effect. All experiments use identical convective latent heating variability, but the large‐scale horizontal wind profile is varied to investigate relationships between stratospheric gravity waves and zonal winds at different levels. Results show that the observed long vertical wavelength gravity waves are primarily sensitive to stratospheric zonal wind variations, while tropopause wind variations have only a very small effect. Thus, neither the critical level filter mechanism nor the obstacle source play much of a role in the observed intraseasonal gravity wave variations. Instead, the results suggest that the stratospheric waves follow the MJO precipitation sources, and tropopause wind anomalies follow the same sources. We further find evidence of intraseasonal wave drag effects on the stratospheric circulation in reanalyzed winds. The results suggest that waves drive intraseasonal stratospheric zonal wind anomalies that descend in altitude with increasing MJO phases 3 through 7. Eastward anomalies descend farther than westward, suggesting that MJO‐related stratospheric waves cause larger eastward drag forces. Key Points: Numerical experiments investigate previously observed relations between intraseasonal stratospheric gravity wave and tropopause zonal wind variability Long vertical wavelength stratospheric wave variance is insensitive to MJO tropopause wind variations but highly sensitive to stratospheric winds Intraseasonal stratospheric zonal wind anomalies, likely driven by wave drag, are found to descend in altitude with increasing MJO phases 3 through 7